Antibacterial and antibiofilm activity of N-aryl derivatives of benzimidazole, benzotriazole and their hybrids - R. S. Begunov; D. O. Egorov; A. V. Chetvertakova; A. I. Khlopotinin; L. I. Savina; V. A. Vinogradova; A. A. Zubishina (Антибиотики и Химиотерапия)
Background. The growing number of multidrug-resistant bacterial strains causing intractable infectious diseases has become one of the serious problems of the 21st century. Therefore, new drugs that act against resistant microorganisms are urgently needed.The aim of the study. Comparison of the ability to inhibit the growth and formation of biofilms of Gram-positive Bacillus subtilis and Gram-negative Pseudomonas aeruginosa, Escherichia coli bacteria with compounds containing one or two pharmacophore polyazaheterocycles.Material and methods. The antibacterial activity of polyazaheterocycles was evaluated by serial dilution at a concentration of 31.25–1000 µg/ml against planktonic forms and biofilms of Pseudomonas aeruginosa PAO1, Escherichia coli AB1157, and Bacillus subtilis BKM B-407. The minimum inhibitory concentration (MIC₅₀) was defined as the concentration of the test compound that suppresses bacterial growth by 50% after 24 hours of incubation. Trifluoromethylbenzene derivatives containing benzimidazole and/or benzotriazole cycles were used as test compounds.Results. The antibacterial and antibiofilm activity of N-aryl derivatives of benzimidazole, benzotriazole and hybrids based on them were studied. Compounds containing the benzimidazole cycle had a greater antibacterial effect compared to analogues with a benzotriazole fragment. New hybrid materials are capable of inhibiting bacterial pathogenicity factors, such as the ability to form biofilms. The presence of a methyl and trifluoromethyl substituent in the second position of benzimidazole enhanced the antibiofilm activity of the hybrid molecule.Conclusion. The presence of a benzimidazole cycle in the compound is a prerequisite for the manifestation of high antimicrobial activity. The synergism of the action of two azaheterocycles — benzimidazole and benzotriazole — in a hybrid compound on bacterial biofilm formation, which is an important virulence determinant, was observed. The resulting hybrid substances are promising compounds for the development of new antibacterial drugs against resistant bacteria.